Strategic Analysis of the North Sumatra Regional Development Planning Agency in the Development of Bumdes and the Village Economy - Ahmad Fikri Ihsan Nasution; Marliyah Marliyah (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The North Sumatra Regional Development Planning Agency is a government agency or agency that aims to coordinate development in the North Sumatra region. This study was conducted by the Regional Planning and Development Agency (BAPPEDASU) of North Sumatra. This study uses qualitative research methods with exploratory research types with data collection methods through observation, interviews and documentation. The selection of informants in this study was based on purposive sampling.